DISPENSASI NIKAH PASCA PERUBAHAN BATASAN USIA MENIKAH DI PENGADILAN AGAMA (TINJAUAN MASLAHAH MURSALAH) - Nur Rahmah; Muhammad Ridho (IAIN Padangsidimpuan, 2023)
Amendments to Law Number 16 of 2019 concerning Marriage focus on the provisions of Article 7 concerning the minimum age limit for marriage to 19 years for men or women. The change in the age limit for marriage has an impact on the high number of applications for marriage dispensation in every religious court. The legal considerations of a Judge in making a Legal Determination/ Decision in an approved Marriage Dispensation Application are crucial to be examined because these considerations do not seem to go hand in hand or reject changes to the marriage age limit. Legal considerations by judges in marriage dispensation cases can be seen in three categories, First, avoiding sin or adultery, Second, because of pregnancy, and Third, adat (larian). The acceptance of the application for Dispensation of Marriage in the three categories is considered on the side of benefit for the prospective husband and wife with the aim of maintaining the status of mother and child, and closing opportunities for the practice of unregistered marriages.The stipulation contains legal certainty, justice and benefits for the parties concerned.